Un autre palimpseste. L’hypertextualité genettienne à l’épreuve de l’intertextualité médiévale : l’exemple des « lais bretons » moyen-anglais - Mireille Séguy (Perspectives Médiévales)
The definitions put forward by Gérard Genette in Palimpsestes have enabled to study central forms of rewriting in medieval literature in a new way. But they have also highlighted the resistance of a literature where “the intertextual current is everywhere” (Zumthor) to an essentially analytical and chronological approach to the phenomena of hypertextuality. What happens to the Genettian palimpsest when it is brought into contact with this diffuse and omnipresent intertextual current? This article attempts to answer this question by focusing on the Middle English lais, in which the practice of rewriting is decisive in the relationship they have with the recomposed family of the “Breton lais”. It thus highlights the significance of another palimpsest, no longer vertical, but horizontal and multidirectional, which is in line with contemporary theories that insist on the importance of the actualization of the possibilities of a text and the primacy of memory in the manufacture of intertextuality.